Dependence of Pin Surface Roughness for Friction Forces of Ultrathin Perfluoropolyether Lubricant Film on Magnetic Disks by Pin-on-Disk Test. (26th December 2012) - Tani, H.; Mitsuya, Y.; Kitagawa, T.; Tagawa, N.
Abstract : We fabricated supersmooth probes for use in pin-on-disk sliding tests by applying gas cluster ion beam irradiation to glass convex lenses. In the fabrication process, various changes were made to the irradiation conditions; these included one-step irradiation of Ar clusters or two-step irradiation of Ar and N2 clusters, with or without Ar cluster-assisted tough carbon deposition prior to N2 irradiation, and the application of various ion doses onto the surface. We successfully obtained probes with a centerline averaged surface roughness that ranged widely from 1.08 to 4.30 nm. Using these probes, we measured the friction forces exerted on magnetic disks coated with a molecularly thin lubricant film. Perfluoropolyether lubricant films with different numbers of hydroxyl end groups were compared, and our results indicated that the friction force increases as the surface roughness of the pin decreases and that increases as the number of hydroxyl end groups increases.